2001
DOI: 10.1111/j.1944-9720.2001.tb02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of EFL Readers' Summary Writing: A Study with Korean University Students

Abstract: This study reports part of the findings of a study of Korean EFL students' skill in summarizing an English text. The participants were 70 freshmen who were assumed to possess the typical Korean EFL students' characteristics related to summary writing. The two English texts employed were expository texts taken from a college‐level ESL reading book. One of the texts (i.e., Text A)was assumed to be easier than the other (i.e., Text B). Data gathered from two summaries were analyzed in terms of the content idea un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 24 publications
(29 reference statements)
1
41
0
7
Order By: Relevance
“…Summarizing, one of the primary writing-to-read strategies in academic settings, offers tremendous opportunities for writing to enhance reading (Kintsch & Van Dijk, 1978;Trites & McGroarty, 2005). Many investigations in L1 settings have demonstrated that summary writing improves reading comprehension of texts (Kim, 2001;Keck, 2006), L2 research has also found substantial impact of summarization on the reading comprehension of EFL learners (Baleghizadeh & Babapur, 2011;Trabasso & Bouchard, 2002;Shokrpour, Sadeghi & Seddigh, 2013). However, research has seldom been done to include summary writing as part of the instruction to ascertain whether it can actually lead to better reading comprehension in EFL settings (Huang, 2014).The current study was conducted to investigate the effects of EFL students' summary writing ability in measuring their reading comprehension.…”
mentioning
confidence: 99%
“…Summarizing, one of the primary writing-to-read strategies in academic settings, offers tremendous opportunities for writing to enhance reading (Kintsch & Van Dijk, 1978;Trites & McGroarty, 2005). Many investigations in L1 settings have demonstrated that summary writing improves reading comprehension of texts (Kim, 2001;Keck, 2006), L2 research has also found substantial impact of summarization on the reading comprehension of EFL learners (Baleghizadeh & Babapur, 2011;Trabasso & Bouchard, 2002;Shokrpour, Sadeghi & Seddigh, 2013). However, research has seldom been done to include summary writing as part of the instruction to ascertain whether it can actually lead to better reading comprehension in EFL settings (Huang, 2014).The current study was conducted to investigate the effects of EFL students' summary writing ability in measuring their reading comprehension.…”
mentioning
confidence: 99%
“…Summary writing is denoted as the process of producing a more concise text by selecting important information and deleting other supporting and explanatory details from the source text (Abdi et al, ; Idris et al, ; Kim, ; Kirkland & Saunders, ). Summarizing skills appear to be integral in comprehending a text, hence, have been employed to evaluate students' understanding in secondary and tertiary education in most ASEAN nations (Abdi et al, ; Idris et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a substantial number of studies have investigated summary writing, only a handful have initiated innovative techniques that have led to summary writing enhancement (Abdi, Idris, Alguliyev, & Aliguliyev, 2016;Cho, 2012;Friend, 2001;Idris, Baba, & Abdullah, 2011;Ke & Hoey, 2014;Marzec-Stawiarska, 2016;McDonough, Crawford, & De Vleeschauwer, 2014;Sung, Liao, Chang, Chen, & Chang, 2016;Wichadee, 2014;Yang, 2015). Obviously, some students have poor summary writing skill, particularly among English as a second language (ESL) students (Hosseinpur, 2015;Idris et al, 2011;Kim, 2001;McDonough et al, 2014;Wichadee, 2014). Summary writing reflects repetition of sections from the original text with absence of comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kim (2001) analyzed the errors in 60 Korean university EFL learners' summary writing and found that syntactic errors were the most damaging, followed closely by lexical errors. Cheng (1994) examined 455 errors in the English compositions produced by six first-year English majors and three second-year English majors from a Chinese university in Beijing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since its boom in 1970s, numerous studies have been done to describe and categorize errors at sentence, paragraph and discourse levels (Cheng, 1994;Frantzen, 1995;Hyland & Anan, 2006;Khuwaileh & Shoumali, 2000;Kim, 2001;Tang, 2000). For example, Kim (2001) analyzed the errors in 60 Korean university EFL learners' summary writing and found that syntactic errors were the most damaging, followed closely by lexical errors.…”
Section: Literature Reviewmentioning
confidence: 99%